Minicursos temáticos como estratégia de sensibilização para a educação e segurança no trânsito: a física no trânsito - Cabral, Fernanda Carolina Freitas (2016)
The Thematic Short Courses project with an awareness strategy for physics teaching came from a recurring social problem and which impact is reflected in the daily lives of all of us, the traffic. This issue can be approached in the classroom through the awareness to the subject, for this reason, it is possible that such knowledge can incorporate its own meanings in Physics Teaching and it starts to make sense in the student's daily life. This study aimed to evaluate the role of Traffic Education and associate it to Physics Teaching so as to promote changes in behavior, even though it is a long-term change, of future drivers. Students from the second year of High School Education (Junior year) of a state educational institution in the city of Manaus participated in this survey. The theoretical framework adopted was the meaningful learning by David Ausubel, that provides guidance on the use and the benefit of student’s previous knowledge. This research describes the development of educational activities through the short courses of Physics, characterized as an educational product and it also reports a particular experience in the classroom in order to enable a more critical education regarding Newton's Laws, so that it can be reproduced and improved.